The impact of experience and familiarity on potential customers’ interest in accelerators considering demographical characteristics - Stirner, Lisa (2018)
In order to adapt to the shift from traditional to relationship marketing, companies are increasingly building long-term relationships with prospective customers from early on. Up to now, no relevant research has been conducted within the field of relationship management and possible variables that influence consumers’ interest in accelerators considering demographical characteristics. To fill the scientific gap, the relationships between experience and familiarity, and the interest to work together with a company are examined, using the Portuguese company Beta-i as an example. The data consists of 224 responses and has been collected via an online survey. Results show (1) work and educational experience, industry familiarity and brand familiarity do not significantly predict the interest in working together with a company – and (2) the reliability of the work and educational experience construct is considered unacceptable. Additionally, (3) the proposition that industry and brand familiarity have an influence on the interest in working together with Beta-i is supported, whereas (4) demographical characteristics do not moderate the relationship. Furthermore, (5) the most adequate marketing approaches for companies are organized workshops, informal get-togethers and holding a course at university. The findings emphasize the benefits of relationship marketing and help managers to implement tools to build a long-term relationship with consumers and increase industry and brand familiarity. Due to the inadequate reliability of the study, future research needs to extend the model by adding more reliable independent variables.